Neoadjuvant irinotecan, cisplatin, and concurrent radiation therapy with celecoxib for patients with locally advanced esophageal cancer. Issue 1 (December 2016) - Cleary, James; Mamon, Harvey; Szymonifka, Jackie; Bueno, Raphael; Choi, Noah; Donahue, Dean; Fidias, Panos; Gaissert, Henning; Jaklitsch, Michael; Kulke, Matthew; Lynch, Thomas; Mentzer, Steven; et al.
Abstract Background Patients with locally advanced esophageal cancer who are treated with trimodality therapy have a high recurrence rate. Preclinical evidence suggests that inhibition of cyclooxygenase 2 (COX2) increases the effectiveness of chemoradiation, and observational studies in humans suggest that COX-2 inhibition may reduce esophageal cancer risk. This trial tested the safety and efficacy of combining a COX2 inhibitor, celecoxib, with neoadjuvant irinotecan/cisplatin chemoradiation. Methods This single arm phase 2 trial combined irinotecan, cisplatin, and celecoxib with concurrent radiation therapy. Patients with stage IIA-IVA esophageal cancer received weekly cisplatin 30 mg/m2 plus irinotecan 65 mg/m2 on weeks 1, 2, 4, and 5 concurrently with 5040 cGy of radiation therapy. Celecoxib 400 mg was taken orally twice daily during chemoradiation, up to 1 week before surgery, and for 6 months following surgery. Results Forty patients were enrolled with stage IIa (30 %), stage IIb (20 %), stage III (22.5 %), and stage IVA (27.5 %) esophageal or gastroesophageal junction cancer (AJCC, 5th Edition). During chemoradiation, grade 3–4 treatment-related toxicity included dysphagia (20 %), anorexia (17.5 %), dehydration (17.5 %), nausea (15 %), neutropenia (12.5 %), diarrhea (10 %), fatigue (7.5 %), and febrile neutropenia (7.5 %). The pathological complete response rate was 32.5 %. The median progression free survival was 15.7 months and the median overall survival was 34.7 months. 15 % (n = 6) of patients treated on this study developed brain metastases. Conclusions The addition of celecoxib to neoadjuvant cisplatin-irinotecan chemoradiation was tolerable; however, overall survival appeared comparable to prior studies using neoadjuvant cisplatin-irinotecan chemoradiation alone. Further studies adding celecoxib to neoadjuvant chemoradiation in esophageal cancer are not warranted. Trial registration Clinicaltrials.gov:NCT00137852, registered August 29, 2005.